Tree growth is better explained by absorptive fine root traits than by transport fine root traits - Anvar Sanaei; Fons van der Plas; Hongmei Chen; Sophie Davids; Susanne Eckhardt; Justus Hennecke; Anja Kahl; Yasmin Möller; Ronny Richter; Jana Schütze; Christian Wirth; Alexandra Weigelt (Communications Biology)
Abstract Although the interest in root traits has increased in recent years, we still have limited knowledge of (i) whether functionally different fine roots—absorptive versus transport roots—have similar trait coordination and (ii) how they help to explain plant performance, such as growth. We measured traits of 25 European broadleaved tree species growing in a research arboretum to study (i) the coordination of root traits within absorptive and transport fine roots and (ii) the degree of trait-tree growth relationships. To do so, we combined a suite of morphological and anatomical traits for each of the absorptive and transport roots. Despite remarkable differences in average trait values between absorptive and transport roots, our study shows that trait coordination within absorptive and transport roots is relatively similar. Our results also show that, for the selected traits, tree growth is better explained by absorptive root traits than by transport root traits and is higher in species with thinner roots. The stronger relationship between absorptive roots and tree growth highlights that roots mostly involved with resource absorption are more important in explaining tree growth than transport roots, which are mainly responsible for resource transportation.